Evaluasi Sistem Pengendalian Internal atas Sistem Pembelian Bahan Baku berdasarkan Kerangka Kerja Terintegrasi Pengendalian Internal COSO Pada PT Chitose Internasional Tbk - Naura Zalfa; Khozin Arief (Indonesian Accounting Literacy Journal, 2021)
This research aims to evaluate the internal control system for the raw material purchasing system based on COSO's internal control integrated framework in PT Chitose Internasional Tbk. The type of the research is a qualitative descriptive which conduct case study of company conditions by providing and describing data in general and systematically due to actual conditions based on five components of COSO’s internal control. The research data used is subject data which obtained by conduct direct interviews with the company and documentary data are obtained from company history, organizational structure, standard operational procedures, and documents used in the purchasing system. Data analysis tool used is control matrix. The result of the research showed that the internal control system for the raw material purchasing system in PT Chitose Internasional Tbk is effective and appropriate with COSO's Internal Control Integrated Framework.